2019
DOI: 10.1097/pq9.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Project to Increase Mother’s Milk Use in an Inner-City NICU

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…After removing duplicates, the titles/abstracts of 69 articles were screened, and 49 articles were excluded. We reviewed the full text of 20 studies; 16 studies (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) were included in systematic review and four studies (33)(34)(35)(36) were excluded because of insufficient primary outcomes or same study cohort; 13 studies were included in the meta-analysis for the primary outcome (17-21, 23, 24, 27-32), another 3 studies were excluded due to insufficient dichotomous data. Figure 1 shows the detailed flow chart.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates, the titles/abstracts of 69 articles were screened, and 49 articles were excluded. We reviewed the full text of 20 studies; 16 studies (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) were included in systematic review and four studies (33)(34)(35)(36) were excluded because of insufficient primary outcomes or same study cohort; 13 studies were included in the meta-analysis for the primary outcome (17-21, 23, 24, 27-32), another 3 studies were excluded due to insufficient dichotomous data. Figure 1 shows the detailed flow chart.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the detailed flow chart. One study (36) was excluded because it was within the greater Neonatal QI Collaborative of Massachusetts human milk collaborative (26), three other studies (33)(34)(35) were excluded because of insufficient primary outcomes (see Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…39,40 Studies have shown that multimodal approaches to breastfeeding, including peer counseling, breastfeeding teams, and hospital policy changes, yield better results than singular interventions in overcoming barriers to breastfeeding and improving infant health outcomes. [26][27][28][29][30][31][32][33][34][35]39,40 AA mothers face unique barriers to breastfeeding. Support from family, specifically fathers and maternal grandmothers, and friends; attendance of childbirth classes; and community support during prenatal and postnatal periods have been shown to be effective in improving breastfeeding rates among AA mothers.…”
Section: Discussionmentioning
confidence: 99%
“…To bridge the demand supply gap of PDHM, we aimed to increase the donor milk collection at our centre, thus increasing the supply of PDHM at the human milk bank. Many quality improvement initiatives have been taken up to improve MOM and PDHM quality and usage in neonates, [9][10][11][12][13] but none address the issue of increasing donor milk collection from satellite collection centres.…”
Section: Introductionmentioning
confidence: 99%